Cine, narrativa y enseñanza de la filosofía. La iniciación al ámbito filosófico en el bachillerato - García Amilburu, María (Revista Española de Pedagogía, 2018)
Before turning to the question to the usefulness of film and narrative as aids in the teaching of philosophy -which is the main purpose of this paper- 1 briefly consider the nature of the knowledge that is imparted and the characteristics of the people we teach. 1 then consider the convenience of employing rhetoric means, as well as logical resources in teaching, to follow with an analysis of narrative -both realistic and fictional, read in books or watched in films-. I finish with some practical aspects of the use of film in the classroom
Keywords: cine; narrativa; enseñanza; filosofía; Revista Española de Pedagogía; bachillerato